Prevalence and factors contributing to mental health challenges among school-going adolescents: a case of a climate-vulnerable Manafwa Watershed in Uganda - Batte, Charles; Apio, Pamela Okwir; Semulimi, Andrew Weil; Nuwasiima, Shivan; Kasoma, Ronald Mutebi; Mwesigwa, Martin Menya; Twinamasiko, Nelson; Siddharthan, Trishul; Mukisa, John; Mukunya, David; Abaatyo, Joan; Nalugya, Joyce Sserunjogi (BioMed Central, 2024)
Globally, mental health challenges are common among school-going adolescents, with a prevalence of 50.2% and 43.6% for depression and anxiety disorders, respectively. In Northeastern Uganda, a prevalence of 26.6% and 8.6% for anxiety and depressive disorders respectively were reported among children. School-going adolescents are at higher risk of developing these mental health challenges and this could be worsened by natural disasters like landslides. We aimed to determine the prevalence and factors contributing to mental health challenges (having at least one of following; depression, anxiety, anger, disruptive behaviour and social concept) among school adolescents in the Manafwa Watershed area.BACKGROUNDGlobally, mental health challenges are common among school-going adolescents, with a prevalence of 50.2% and 43.6% for depression and anxiety disorders, respectively. In Northeastern Uganda, a prevalence of 26.6% and 8.6% for anxiety and depressive disorders respectively were reported among children. School-going adolescents are at higher risk of developing these mental health challenges and this could be worsened by natural disasters like landslides. We aimed to determine the prevalence and factors contributing to mental health challenges (having at least one of following; depression, anxiety, anger, disruptive behaviour and social concept) among school adolescents in the Manafwa Watershed area.This was a cross-sectional study in 3 districts of the Manafwa watershed area (Bududa, Manafwa, and Butaleja). We selected school-going adolescents aged 13-18 years because of the nature of study tools. Mental health challenges (anxiety, depression, anger, disruptive behaviour and self-concept) were assessed using the Beck Youth Inventory-II. Descriptive statistics and inferential analysis were performed to determine factors associated with mental health challenges.METHODSThis was a cross-sectional study in 3 districts of the Manafwa watershed area (Bududa, Manafwa, and Butaleja). We selected school-going adolescents aged 13-18 years because of the nature of study tools. Mental health challenges (anxiety, depression, anger, disruptive behaviour and self-concept) were assessed using the Beck Youth Inventory-II. Descriptive statistics and inferential analysis were performed to determine factors associated with mental health challenges.A total of 762 adolescents participated, with a median age of 17 years (interquartile range =16-17 years). More than half of the students were females. The prevalence of mental health challenges was 65% with a (confidence interval) = 54.0% - 75.0%; the majority 44% of the participants had anxiety, and 31% had disruptive behaviour. Families with more than five children [adjusted odds ratio = 1.18, 95% confidence interval= 1.08-1.29, p value = <0.001] and substance abuse [adjusted odds ratio = 1.20, 95% confidence interval= 1.15-1.24, p value <0.001] were significantly associated with mental health challenges.RESULTSA total of 762 adolescents participated, with a median age of 17 years (interquartile range =16-17 years). More than half of the students were females. The prevalence of mental health challenges was 65% with a (confidence interval) = 54.0% - 75.0%; the majority 44% of the participants had anxiety, and 31% had disruptive behaviour. Families with more than five children [adjusted odds ratio = 1.18, 95% confidence interval= 1.08-1.29, p value = <0.001] and substance abuse [adjusted odds ratio = 1.20, 95% confidence interval= 1.15-1.24, p value <0.001] were significantly associated with mental health challenges.The prevalence of mental health challenges among students was high with majority having anxiety and disruptive behaviour. Adolescents from families with more than five children and those with substance abuse were more likely to have mental health challenges. We therefore recommend that various stakeholders such as the Ministry of Health, and the Ministry of Education, design a curriculum that caters to the mental health needs of children. Family planning awareness, awareness on Government laws prohibiting alcohol and substance use, and parenting skills should be raised by the local leaders.CONCLUSIONThe prevalence of mental health challenges among students was high with majority having anxiety and disruptive behaviour. Adolescents from families with more than five children and those with substance abuse were more likely to have mental health challenges. We therefore recommend that various stakeholders such as the Ministry of Health, and the Ministry of Education, design a curriculum that caters to the mental health needs of children. Family planning awareness, awareness on Government laws prohibiting alcohol and substance use, and parenting skills should be raised by the local leaders.